Ultrathin highly luminescent two-monolayer colloidal CdSe nanoplatelets - Delikanli, Savas (2020)
Surface effects in atomically flat colloidal CdSe nanoplatelets (NLPs) are significantly and increasingly important with their thickness being reduced to subnanometer level, generating strong surface related deep trap photoluminescence emission alongside the bandedge emission. Herein, colloidal synthesis of highly luminescent two-monolayer (2ML) CdSe NPLs and a systematic investigation of carrier dynamics in these NPLs exhibiting broad photoluminescence emission covering the visible region with quantum yields reaching 90% in solution and 85% in a polymer matrix is shown. The astonishingly efficient Stokes-shifted broadband photoluminescence (PL) emission with a lifetime of ≈100 ns and the extremely short PL lifetime of around 0.16 ns at the bandedge signify the participation of radiative midgap surface centers in the recombination process associated with the underpassivated Se sites. Also, a proof-of-concept hybrid LED employing 2ML CdSe NPLs is developed as color converters, which exhibits luminous efficacy reaching 300 lm Wopt−1. The intrinsic absorption of the 2ML CdSe NPLs (≈2.15 × 106 cm−1) reported in this study is significantly larger than that of CdSe quantum dots (≈2.8 × 105 cm−1) at their first exciton signifying the presence of giant oscillator strength and hence making them favorable candidates for next-generation light-emitting and light-harvesting applications.